FUZZY EPISTEMOLOGY FROM VIEW POINT OF MYSTICAL THEOLOGY - Vakili, Hadi (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
The issue of immanence and transcendence is crucial for religious thought. One reason why that is never resolved is that it has so many meanings and turns up in so many diff erent contexts. A view may emphasize immanence in one context and emphasize transcendence in another. What the terms mean depends in part on the metaphysical assumptions, usually unconscious, of those who use them. According to Ibn al-â€˜ArabÄ«, these two mutually dependent sides must constantly be borne in mind, if the relationship between God and universe, Reality and appearance, is to be truly understood. It is because of nonexistence that God is described as transcendent (tanzÄ«h), and because of existence that He is known as immanent (tashbÄ«h). h e two aspects of God, transcendence and immanence, are summarized for Ibn al-â€˜ArabÄ« by the Qurâ€™anic verse â€œThere is nothing like Him, and He is the Hearer, the Seerâ€ (42.11). The religious-historians and researchers and alongside them some mystics insist on it and according to it they consider the logic of the call as a function of the two-valued logic (transcendence or immanence). According to this logic one must classify the call of the divine prophets based on their emphasis upon the unity or plurality in three categories of Transcendental calls, Similar calls and Transcendent-Imminent (TI) calls and as a result consider the face of divine religions necessarily either Transcendental or Similar or T-I. Fuzzy logic and thought has in understanding of propositions approaches paradoxes and also, in general of any mystical explanation and analysis.